Them and Image in Najiīb Maḥfūẓ Novels of 1960’s - Bermawy Munthe (Al-Jami'ah Research Centre, 1993)
The theme of a novel is one of its most important elements. Robert Pewn Warren says, “the theme is what a piece of fiction stacks up to. It is the idea, the significance, the interpretation of personal and events, the pervasive and unifying view of life which is embodied in the total narrative.” Najīb Maḥfūẓ, the most outstanding contemporary Egyptian novelist of Arabic literature, had a new theme in his works of the 1960’s. Some Critics say that Najīb Maḥfūẓ had a clear preoccupation, which is the search for a universal ideology of truthfulness and psychological satisfaction. This vision is actualized clearly in his novels of the 1960’s al-Liṣṣ wa al-Kilāb (the thief and the dogs, 1961) al-Summān wa al-Kharīf (Quail and Autumn, 1962), al-Ṭariq (the Search, 1964), al-Shaḥḥādh (the begger, 1965), Tharthara Fauq al-Nīl (Chattring on the Niel, 1966) and mirāmar (the name of a person, 1967).